Impact of positive surgical margin length and Gleason grade at the margin on biochemical recurrence in patients with organ‐confined prostate cancer. Issue 16 (25th September 2019) - Preisser, Felix; Coxilha, Gilberto; Heinze, Alexander; Oh, Su; Chun, Felix K‐H.; Sauter, Guido; Pompe, Raisa S.; Huland, Hartwig; Graefen, Markus; Tilki, Derya
Abstract: Background: Positive surgical margins (PSMs) represent a poor prognostic factor at radical prostatectomy (RP). To investigate the impact of PSM, its length, the focality, and the PSM Gleason, on biochemical recurrence (BCR) in organ‐confined RP patients. Methods: Within a high‐volume center database, we identified patients who harbored organ‐confined (pathologic stage T2 disease) prostate cancer (PCa) at RP (2010‐2016). Kaplan‐Meier analyses and multivariable Cox regression models were used to test the effect of the PSM on the BCR risk. Results: Overall, 8770 patients were identified. Of those, 6.6% (n = 579) harbored PSM. BCR‐free survival at 72 months after RP was 77.7% vs 89.0% for patients with vs without PSM ( P < .001). BCR‐free survival rates at 72 months were 77.4% vs 73.6% ( P = .1) for unifocal vs multifocal PSM, 77.2% vs 71.8% ( P = .03) for Gleason pattern 3 vs ≥4 at the margin and 88.4% vs 66.3% ( P < .001) for <3 vs ≥3 mm length of margin. In multivariable Cox models PSM was an independent predictor for BCR (hazard ratio [HR] = 2.40, P < .001). However, in subgroups with PSM, only ≥3 mm PSM represented an independent predictor (HR = 1.93, P = .04), while focality and Gleason at the margin were no significant predictors. Conclusion: PSM represents an independent predictor for BCR in organ‐confined PCa at RP. Moreover, Gleason ≥4 at the margin and ≥3 mm PSM length were associated with worse BCR‐free survival. Closer surveillance of patients with organ‐confined PCa at RP and PSM can help to identify those who qualify for early salvage radiotherapy.